The Differences of Neo-Kantian and Hartmannian Theories of Knowledge - Juršėnas, Nikodemas (Problemos, 1979)
The causes of the origin of the German neo-Kantianism are observed. Among those are the Marburg and Baden schools, different stages of the development of these tendencies and trends. The relations of neo-Kantians to I. Kant are discussed. An attempt is made to discover a specific character of their approach to the problems of cognition. The next problem under discussion is N. Hartmann’s deviation from neo-Kantians and the later opposition of his critical ontology to the subjective idealistic position of P. Natorp and other neo-Kantians.